Outcomes of robotic surgery for endometrial cancer in elderly women. (June 2020) - Hotton, Judicael; Koual, Meriem; Gosset, Marie; Rossi, Lea; Delomenie, Myriam; Ngo, Charlotte; Lecuru, Fabrice; Bats, Anne-Sophie
Abstract: Introduction: Few data have been reported on robot-assisted surgery in elderly. The objectives were to compare feasibility, complication data, and survival of patients under and upper the age of 70 who are managed for endometrial cancer by robot-assisted laparoscopy. Materials and methods: This is a retrospective comparative single-center study including patients treated between January 2007 and December 2016. Patients were divided into 2 groups: less than 70 years and greater than or equal to 70 years. The primary endpoint was the rate of complications. The secondary endpoints were conversion rate and follow-up. Results: 148 patients were included: 86 under 70 (group A) and 62 aged 70 and over (group B). More adhesiolysis was performed in group B (p < .01); the pelvic and para-aortic lymph node dissection rates were not different between both groups (p = .2 and p = .9). The operating times were significantly longer in group B (220.1 vs. 234.4 min, p = .02). The conversion rate was similar between the 2 groups (p = .7). The tumors were endometrioid adenocarcinomas for 77.9 and 66.7% respectively (p = .2), with grade 3 tumors more represented in older patients (24.4% vs. 48.4%, p < .01). There were more tumors at high risk of recurrence after 70 years (33.7 vs. 45.2%, p = .04). No significant difference was found for postoperative complications. There was no difference in overall survival (p = .7) or progression-free survival (p = .2). Undertreated women rate was similar in both groups (p = .1). Conclusion: Robotic surgery appears feasible and reproducible and could bring a benefit and allow optimal surgery without increasing the morbidity in the management of endometrial cancers whatever the age is. Highlights: We compared the robotic management of endometrial cancer in patients ≥ 70 years and <70 years. Elderly patients have more advanced and aggressive cancers. They benefit from as much lymph node dissections despite more advanced stages. Robot-assisted laparoscopy is feasible in elderly with similar complications rates. There is no difference in survival.